THE INFLUENCE OF RELIGIUS, BANK PRODUCTS AND IMAGE ON CUSTOMERS' DECISIONS TO SAVE AT BPRS AMANAH INSAN CITA - lestari, putri; Hasanah, Uswah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research aims to determine the influence of religiosity, products and bank image on customer decisions at BPRS Amanah Insan Cita. This type of research is quantitative research. The sampling technique in this research was a purposive sampling technique using saturated samples where the total sampling was determined by customers at BPRS Amanah Insan Cita, totaling 32 customers. The reason for using the entire population as a sample is because it represents the entire population because if the population is less than 100, then the entire research sample is used, therefore the researcher took 32 samples taken from all customers. The variables in this study are divided into independent variables (X) and dependent variables (Y). Independent variables include religiosity (X1), product (X2) and company image (X3), while the dependent variable is the decision to save (Y). The research results show that there is a partial influence of religiosity, products and bank image on customer decisions at BPRS Amanah Insan Cita. This can be seen from the results of the t test on each variable where the significant value is